1983
DOI: 10.1159/000123442
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Pattern of Follicle Stimulating and Luteinizing Hormone Responses to Gonadotropin-Releasing Hormone in vitro

Abstract: Increasing concentrations of LHRH or its active analog des-gly10 (D-ala6) LHRH induced a bimodal pattern of FSH and LH release from incubated male rat pituitaries. A low amplitude response (40% increase of LH over baseline levels) was observed for concentrations of LHRH and the agonist in the range of 10–12 and 10–13 M respectively. After a plateau of gonadotropin stimulation, a further high amplitude response (180–240% increase over baseline levels) occurred between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Specific activity was close to 2.000 Ci/mmol. The nonradioactive peptide content of the preparation was negligible when measured by radioimmunoassay [16] using an antibody raised against the N-terminal fragment of the GnRH molecule [17], The maximum binding capacity to an excess of pituitary membrane preparation was 30%.…”
Section: Quantitative Auloradiographvmentioning
confidence: 97%
“…Specific activity was close to 2.000 Ci/mmol. The nonradioactive peptide content of the preparation was negligible when measured by radioimmunoassay [16] using an antibody raised against the N-terminal fragment of the GnRH molecule [17], The maximum binding capacity to an excess of pituitary membrane preparation was 30%.…”
Section: Quantitative Auloradiographvmentioning
confidence: 97%
“…By calculation of the release rate, Koninckx et al (1976) showed a biphasic FSH release in women. Consistent with this finding in vitro experiments have demonstrated a clear biphasic FSH release pattern with a time course almost similar to that of LH {Eddie et al 1982;Jenner, de Koning and van Rees 1982;Leblanc, Pattou, VHeritier, Gogan, Slama and Kordon 1983;Waring and Turgeon 1983). Our in vivo study also demonstrates a biphasic FSH response (in both eugonadal and oligospermic men).…”
Section: Discussionmentioning
confidence: 60%
“…The iodination mixture was applied to a (0.9 x 10 cm) column, and eluted with increasing molarity of acetic acid; 1 ml fractions were collected. Unlabelled hormone was assayed in an RIA using an antibody raised against the N-terminal fragment of GnRH (41). It was readily eluted by 1.75 mM acetic acid, whereas labelled GnRH was eluted in two peaks at higher acetic acid concentrations (8 mM).…”
Section: Ligand Iodinationmentioning
confidence: 99%